Improving indoor comfort through façade improvement for residents in Basra, Iraq - Al-hambosh, Ziadoon Ahmed Mazyed (2023)
Indoor thermal comfort is key to residents’ comfort in the dry and hot regions. In Iraq, the climate has changed due to several factors such as wars and economic crises. This led to extremely high temperatures. This phenomenon has resulted in significant energy use and discomfort for the residents ‘of Basra. In a hot, arid country like Iraq, the residents’ thermal comfort is still the main problem, especially during summertime resulting a high energy usage. Therefore, this research aimed to determine the optimum façade improvement that Basra people can use to attain indoor thermal comfort. This study employed an experimental design based on Fanger's model to analyse variables that may impact indoor comfort and determine a balance between air quality and indoor comfort. Vi suit and 3D blender software were used in the simulation to examine the impact of thermal on the residents' façade. The experiment result indicated that double-glazing typologies and double-skin façade materials could increase inhabitants' indoor thermal comfort by 50 % and enhance air quality by 40%. Using these façade materials and typology could potentially improve indoor comfort for the residents. This study is limited to understanding the effect of double glazing and double skin materials on residents in arid and hot climates particularly in the Basra City, Iraq. The development of façade improvement could formulate future guidelines and policies for façade treatment in hot and arid countries.